A low-power magnetorheological fluid clutch utilizing electropermanent magnet arrays - Bira, Nicholas; Dhagat, Pallavi; Davidson, Joseph R. (Frontiers in Materials, 2022)
In this work, we develop a compact, low-power and partially 3D-printed magnetorheological fluid (MRF) clutch that operates by variably and reversibly altering the shear stress of the fluid through the local activation of an array of electropermanent magnets (EPMs). By toggling the magnetization of each EPM independently on the order of a few milliseconds, we allow for rapid response times and variable torque transmission without further power input. Selectively polarizing the EPMs for different lengths of time results in repeatable and variable magnetic flux, in turn enabling further control precision. We present the design, modeling, and measured performance of this clutch with various control strategies, and demonstrate its utility as a low-power alternative to more traditional clutch designs.